$$BR^3_{1}(Q^3_{2},-)\quad U=\pmatrix{1 & 2 & 3 \cr 1 & 3 & 2 \cr 1 & 3 & 2}\quad D=\pmatrix{1 & 3 & 2 \cr 1 & 2 & 3 \cr 1 & 2 & 3}\quad \hbox{order 4} \quad c_1 = 2, c_2 = 0$$ $$BR^3_{2}(Q^3_{2},Q^3_{2})\quad U=\pmatrix{1 & 2 & 3 \cr 1 & 2 & 3 \cr 2 & 1 & 3}\quad D=\pmatrix{1 & 2 & 3 \cr 1 & 2 & 3 \cr 2 & 1 & 3}\quad \hbox{order 2} \quad S, c_1 = 2, c_2 = 0$$ $$BR^3_{3}(-,Q^3_{2})\quad U=\pmatrix{1 & 3 & 2 \cr 1 & 2 & 3 \cr 1 & 2 & 3}\quad D=\pmatrix{1 & 3 & 2 \cr 1 & 3 & 2 \cr 1 & 3 & 2}\quad \hbox{order 4} \quad c_1 = 4, c_2 = 2$$ $$BR^3_{4}(Q^3_{1},-)\quad U=\pmatrix{3 & 1 & 2 \cr 3 & 1 & 2 \cr 3 & 1 & 2}\quad D=\pmatrix{1 & 2 & 3 \cr 1 & 2 & 3 \cr 1 & 2 & 3}\quad \hbox{order 6} \quad c_1 = 6, c_2 = 0$$ $$BR^3_{5}(Q^3_{1},-)\quad U=\pmatrix{3 & 2 & 1 \cr 1 & 2 & 3 \cr 3 & 2 & 1}\quad D=\pmatrix{1 & 2 & 3 \cr 1 & 2 & 3 \cr 1 & 2 & 3}\quad \hbox{order 4} \quad c_1 = 4, c_2 = 2$$ $$BR^3_{6}(Q^3_{1},-)\quad U=\pmatrix{3 & 2 & 1 \cr 3 & 2 & 1 \cr 3 & 2 & 1}\quad D=\pmatrix{1 & 2 & 3 \cr 1 & 2 & 3 \cr 1 & 2 & 3}\quad \hbox{order 4} \quad c_1 = 6, c_2 = 0$$